PENGARUH PENGGUNAAN METODE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR SISWA KELAS V MI AT-TAUHIDIYAH PADA PEMBELAJARAN TEMATIK - Meliantina Meliantina; Nasrodin Nasrodin; Yunia Dwi Arini (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2022)
This study aims to determine the effect of using the NHT (Numbered Head Together) Method on the learning outcomes of fifth grade students at Madrasah Ibtidaiyah At - Tauhudiyah on thematic learning. This type of research is pre experimental designs, which are parts of One Group Pretest - Posttest design. The population in this study were all of the students of fifth grade in Madrasah Ibtidaiyah At Tauhidiyah Sumberarum which are 25 students. The sample used in this study was all students of fifth grade. The sampling technique is using nonprobability sampling, this technique includes a variety of techniques among others is saturated sampling. This research instrument uses multiple choice test items, specifically 25 items. The collected data is processed using descriptive statistical analysis, normality test, homogeneity test, and hypothesis test by using SPSS 16.0 for windows application. Based on the results of SPSS 16 the output on the hypothesis testusing Paired Sample t Test conducted on student learning outcomes data shows the results of pretest 70.80 and posttest of 85.64 getting an increase in the amount of 14.24. This is provend by the results of t Test with t count -9,401 and t table 1,711 with sig tailed 0.00 <0.05 with a correlation level of 0.664. So the conclusion is that Ho is rejected and Ha is accepted, which is there is an influence of using the NHT (Numbered Head Together) Method on the learning outcomes of fifth grade students at MI At Tauhidiyah on thematic learning